Thrombolysis in Deep Vein Thrombosis: Is there still an Indication? - Wells, Philip S.; Forster, Alan J. (Thrombosis and Haemostasis, 2001)
The most accepted therapy for DVT consists of anticoagulation with unfractionated heparin or low molecular weight heparin, followed by variable duration oral anticoagulation but thrombolytic therapy has been proposed in addition to standard anticoagulation. This paper reviews the literature on post thrombotic syndrome, the natural history of vein patency after therapy, and we perform a systematic review, using accepted standards for meta-analysis, to determine the outcomes when thrombolytic therapy is used to treat DVT. We demonstrate that thrombolytic therapy for DVT results in a significant increase in the risk of major hemorrhage and a significant increase in the rate of vein patency. However, although thrombolytic therapy is advantageous over anticoagulation as measured by early vein patency, a benefit in terms of a reduction in PTS risk, is unproven. Our review also shows that there is no evidence that there is a difference in efficacy between thrombolytic agents or that local therapy differs from systemic therapy. Finally, the potential role of catheter directed therapy is unknown since appropriate trials have not been performed but it is reasonable to use catheter directed therapy in patients with phlegmasia cerulea dolens. We conclude that more work is needed to define the role of thrombolytic therapy but it is too early to abandon this therapeutic modality.
Keywords: Thrombolytics; post thrombotic syndrome; deep-vein thrombosis; treatment; bleeding, meta-analysis